Influencia del factor socioeconómico y perfil de egreso en las competencias del artista profesional del egresado de la Escuela Superior de Bellas Artes de Iquitos, 2020 - Panduro Meza, Yara (2023)
The objective of this research was to explain the extent to which socioeconomic factors and graduation profiles influence the skills of professional artists who graduated from the Escuela Superior de Bellas Artes de Iquitos in 2020. The study used an explanatory, non-experimental type and the population size consisted of 80 graduates from the Superior School of Fine Arts. To ensure the validity of the data collection instrument, the Delphi method was employed, along with expert judgement and reliable information through Cronbach’s Alpha. Upon applying the instruments to the study population, the results indicated that 65.0% of graduates demonstrated average professional skills, while 17.5% had good skills and 17.5% had poor skills. In terms of socioeconomic level, 46.3% had a medium level, 27.5% had a low level, and 26.3% had a high level. Lastly, in the graduation profile category, 53.8% had a regular profile, 23.8% had a poor profile, and 22.5% had a good profile. Through bivariate analysis, it was determined that socioeconomic factors and graduation profiles had a highly significant influence on the professional skills of graduates from the Escuela Superior de Bellas Artes in Iquitos. However, in multivariate analysis, it was found that there was no significant influence between the professional skills of the graduates and the variables of socioeconomic level and graduation profile. Statistical tests were conducted with a confidence level of 0.05.